Women of Trachis Sophokles - Kitzinger, Rachel (Lever Press, 2021)
This new translation of Sophokles' Women of Trachis is a living script in conversation with the past. Rachel Kitzinger, a Classicist, and Eamon Grennan, a poet, have captured the tones of ancient Greek in strong, swift English, making this translation suitable for a modern audience, whether as readers, listeners, or viewers. The unique addition of an audio recording of the text performed by Vassar College students contributes to the play's accessibility and vividness. Offering a picture both of domestic life and of the values and expectations that characterize Athenian men, Women of Trachis is a rich resource for those interested in gender roles in Greek antiquity.